Idoma musical instruments - Blench, Roger (International Library of African Music, 1987)
The Idoma are a cluster of peoples inhabiting a vertical strip of southern Central Nigeria, to the north and south of Oturkpo town (Armstrong, 1955a and Hansford et al. 1976). Their population was estimated at a quarter of a million in 1955, but has probably increased substantially since that time. 'Idomoid' is one of the principal branches of South Central Niger Congo and forms a co-ordinate branch with the Nupe languages. Abraham (1967) was the first author to study the Idoma language in detail, and the orthography of Idoma today reflects his original analysis, although it has undergone a certain amount of updating since then.
Keywords: Idoma (African people); Idoma language; African Music; Nigeria